(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
In this paper, the inheritance of valuable economic traits in F1 plants obtained from cross-breeding of fine fiber cotton and large boll lines was analyzed. In the conducted researches, it was observed that the dominance coefficient of cotton was inherited in a positive intermediate, negative intermediate, dominant and extremely dominant state. In order to maintain a positive state of heterosis in the F1 plants obtained as a result of hybridization, it is necessary to continue genetic-selection scientific research in the next generations.